Probabilities of ADD/ADHD and Related Substance Use Among Canadian Adults. Issue 12 (October 2019) - Connolly, Ross D.; Speed, David; Hesson, Jacqueline
Objective: The aim of this study was to estimate the prevalence and probabilities of comorbidities between self-reported ADD/ADHD and smoking, alcohol binge drinking, and substance use disorders (SUDs) from a national Canadian sample.Method: Data were taken from the Public Use Microdata File of the 2012 Canadian Community Health Survey–Mental Health ( N = 17 311). The prevalence of (a) smoking, (b) alcohol binge drinking, and (c) SUDs was estimated among those with an ADD/ADHD diagnosis versus those without an ADD/ADHD diagnosis.Results: After controlling for potential socioeconomic and mental health covariates, self-reported ADD/ADHD acted as a significant predictor for group membership in the heaviest smoking, heaviest drinking, and heaviest drug usage categories.Conclusion: Individuals self-reporting a diagnosis of ADD/ADHD were found to have a significantly higher likelihood of engaging in smoking and alcohol binge drinking, and were more likely to meet criteria for SUDs than individuals not reporting an ADD/ADHD diagnosis.